Edukasi HIV/AIDS “Gerakan 1000 Remaja Millenial Peduli Odha” (Gerserha) di MA Al-Mukhtariyah Kabupaten Bandung Barat - Ami Kamila; Anzhar Ismail (Universitas Lancang Kuning, 2020)
Based on the analysis of the AIDS Commission (KPA) in West Bandung District until July 2019, there were 379 cases of HIV/AIDS with 56 new cases. As many as 53% are involved in free sexual relations, while 52% occur at the age of 21-29 years and 33% are found in the sexual or gay community which also triggers HIV/AIDS transmission and becomes the second largest after heterosexuality. To achieve success, a three zero program needs to be innovative and continuous to increase knowledge about HIV/AIDS in adolescents through counseling to prevent the spread of infection early on. The movement of 1000 Millennial Youth Caring PLWHA is expected to be able to introduce and publish Youth Reproductive Health to prevent sexual freedom that can prevent the spread of HIV/AIDS transmission because adolescent behavior is influenced by their knowledge and attitude regarding reproductive health and HIV / AIDS. The target of this movement is high school teenagers in West Bandung District. The first activity was carried out at MA Al-Mukhtariyah Mande KBB. The activity was carried out in the form of counseling using PowerPoint media, leaflets and videos. Pre-test and post-test carried out before and after the activity which is one form of evaluation of the direct output of this activity. Pre-test and post-test results showed a significant increase from the average pre-test results of 63.8 and post-test results of 89.4. This shows that counseling activities are effective in increasing students' knowledge about HIV and AIDS (p <0.005).